The treatment of painful temporomandibular joint clicking with oral splints: A randomized clinical trial - Rodrigues Conti, Paulo Cesar; dos Santos, Carlos Neanes; Kogawa, Evelyn Mikaela; de Castro Ferreira Conti, Ana Claudia; Pereira de Araujo, Carlos dos Reis (Amer Dental Assn, 2006)
Background. The authors compared the efficacy of bilateral balanced and canine guidance (occlusal) splints in the treatment of temporomandibular joint (TMJ) pain in subjects who experienced joint clicking with a nonoccluding splint in a double-blind, controlled randomized clinical trial.Methods. The authors randomly assigned 57 people with signs of disk displacement and TMJ pain into three groups according to the type of splint: bilateral balanced, canine guidance and nonoccluding. The authors followed the groups for six months using analysis of a visual analog scale (VAS), palpation of the TMJ and masticatory muscles, mandibular movements and joint sounds. They used repeated analysis of variance and a XI test to test the hypothesis.Results. The type of guidance used did not influence the pain reduction; yet both occlusal splints were superior to the nonoccluding splint, on the basis of the VAS. Despite similar outcomes in relation to opening, left; lateral and protrusive movements, TMJ and muscle pain on palpation, subjects who used the occlusal splints had improved clinical outcomes. The frequency of joint noises decreased over time, with no significant differences among groups. Subjects in the groups using the occlusal splints reported more comfort.Conclusion. The type of lateral guidance did not influence the subjects'; improvement: All of the subjects had a general improvement on the VAS, though subjects in the occlusal splint groups had better results that did subjects in the nonoccluding splint group.
Keywords: temporomandibular disorders; occlusion; occlusal splints